From Traditional Grammar to Theme-Based: Teaching English with a Purpose (2017)
ABSTRACT: This action research aimed to contextualize English learning and promote students’ interaction through the use of theme-based activities. In order to achieve these goals, a series of actions were implemented. Firstly, a unit was designed based on a theme. Secondly, appropriate materials and activities were addressed through fourth stages of classroom instruction: introduction, demonstration, practice and assessment. Finally, cooperative work was promoted throughout several of the stages. Data collected for this study included class journals, questionnaires, interviews and students’ artifacts. Data analysis suggested that students become more engaged with activities that have a closer relation to real life and are presented with eye-catching materials. Furthermore, it showed that students improved their English performance as a result of the strategies implemented.